1998
DOI: 10.1038/sj.pcan.4500257
|View full text |Cite
|
Sign up to set email alerts
|

Does a family history of prostate cancer result in more aggressive disease?

Abstract: Current epidemiologic and genetic data suggest the hypothetical paradigm that prostate cancer occurs in three forms: sporadic, familial, and hereditary ( Figure 1). Sporadic cases are not associated with familial inheritance patterns, while familial cancer is de®ned as simple clustering of two or more cases within a family. The existence of hereditary prostate cancer, a subset of the familial form, is suggested by three epidemiologic observations enumerated by Carter et al 1 : (1) relatives of patients younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…As in previous studies (12,13), we found that the risk of PCa was higher in men whose relatives were diagnosed with PCa when they were <60 years old (Table 3). We also observed that, a family history of PCa was equally related to aggressive and non-aggressive PCa (Table 3), which conflicted with previous findings (13,37,38). Similarly, men with a family history of PCa had a significantly higher risk of PCa than men without a family history of the disease, regardless of tumor grade.…”
Section: Discussioncontrasting
confidence: 91%
“…As in previous studies (12,13), we found that the risk of PCa was higher in men whose relatives were diagnosed with PCa when they were <60 years old (Table 3). We also observed that, a family history of PCa was equally related to aggressive and non-aggressive PCa (Table 3), which conflicted with previous findings (13,37,38). Similarly, men with a family history of PCa had a significantly higher risk of PCa than men without a family history of the disease, regardless of tumor grade.…”
Section: Discussioncontrasting
confidence: 91%
“…Family history has been associated consistently with prostate cancer risk in epidemiologic studies 94–111. Prostate cancer appears to have a stronger familial aggregation than colon or breast cancer, two malignancies with well recognized familial components 112.…”
Section: 0 Goalsmentioning
confidence: 99%
“…Several studies found that this risk increased further with additional affected first degree relatives, and the increase in risk due to family history is consistent across countries and ethnic groups studied [20]. In addition, a positive family history may also be associated with a poor prognosis of disease, including both a greater risk of biochemical relapse and metastasis [21]. Given the importance of family history on prostate cancer risk and progression, the identification of genetic factors underlying prostate cancer in family history positive samples can provide valuable markers for diagnosing and treating this disease.…”
Section: Discussionmentioning
confidence: 85%